Entrepreneurial motivation, competency and micro-enterprise sustainability performance: evidence from an emerging economy - Fazal, Syed Ali; Alshebami, Ali Saleh; Al Mamun, Abdullah; Ali, Mohd Helmi; Muniady, Rajennd; Al-Shami, Samer Ali Hussein; Al Marri, Salem Handhal; Seraj, Abdullah Hamoud Ali; Thomran, Murad; Algobaei, Faiz (MDPI, 2022)
Small to medium-sized enterprises suffer from loss of competitive advantage, low productivity, and poor performance because of inadequate competencies. Therefore, the primary objective of this study was to examine the effect of selected motivational dimensions (i.e., self-improvement, self-confidence, openness to change, pull factors, and the need for achievement) on entrepreneurial competency among micro-entrepreneurs. We used a cross-sectional design and collected quantitative data from 403 micro-entrepreneurs in Malaysia using random sampling. SEM-PLS was used for data analysis. The findings revealed that self-confidence, openness to change, and pull factors positively influenced entrepreneurial competencies. Moreover, there was a positive effect of self-confidence, pull factors, need for achievement, and entrepreneurial competency on enterprise sustainability performance. Furthermore, entrepreneurial competencies significantly mediated the effect of self-confidence, openness to change, and pull factors on enterprise sustainability performance. Apart from extending the lens of a resource-based view, this study enriches enterprise sustainability literature from emerging nations’ perspective. Policymakers can strengthen their programs and policies to improve the entrepreneurial competencies of micro-entrepreneurs and their business sustainability.